2004
DOI: 10.1002/elps.200406079
|View full text |Cite
|
Sign up to set email alerts
|

Membrane proteome analysis of the green‐sulfur bacterium Chlorobium tepidum

Abstract: An extensive proteomic approach relies on the possibility to visualize and analyze various types of proteins, including membrane proteins, which are rarely detectable on two-dimensional electrophoresis gels. In this study, different methods were employed for the enrichment of membrane proteins from Chlorobium tepidum prior to analysis with two-dimensional electrophoresis (2-DE). Isolated membranes were solubilized with Triton X-100 and from the supernatant we identified 58 unique proteins. The use of ionic sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 31 publications
1
36
0
1
Order By: Relevance
“…Deisotoped peaks were labeled by the software, and the 100 most intense peaks were used for data base searching. Autolytic tryptic peptides or peptides resulting from the identified protein were used for internal calibration (45).…”
Section: Methodsmentioning
confidence: 99%
“…Deisotoped peaks were labeled by the software, and the 100 most intense peaks were used for data base searching. Autolytic tryptic peptides or peptides resulting from the identified protein were used for internal calibration (45).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, Lmo0927 was identified by one peptide which belongs to the hydrophobic part of the protein (intersection region between TMD 3 and 4). This peptide was detected in section 11 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) while the calculated mass of the total protein is 74.7 kDa.…”
Section: Profiling Of the Membrane Proteome Using Lanespectormentioning
confidence: 99%
“…However, and contrary to the robustness of expression analyses, classical 2-D PAGE still fails to surmount fundamental limitations related to the biochemical properties of the investigated proteins. Hydrophobic proteins as well as those with extreme pI or molecular weight or low-abundant proteins are generally not accessible by 2-D PAGE [9][10][11][12], although noteworthy improvements for membrane proteomics have been established by different groups [13][14][15]. While the restriction with regard to the characterization of low-abundant proteins is usually compensated for by particular biochemical procedures for enrichment of the desired subcellular fraction [16], non-gel based technologies -mainly LC-MS/MS -are generally accepted without reservations even with regard to the other limitations mentioned above [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed it is generally recognized that specific protein losses occur with any kind of organic-based protein denaturation protocol, immediately calling into question the suitability of these extracts for truly quantitative, global proteomics analyses. Nonetheless many groups continue to routinely extract protein from biological samples using somewhat comparable organic precipitation protocols, and some select advantages to this practice are suggested (16,17).…”
mentioning
confidence: 99%